Industrial training report: Universiti Sains Malaysia (USM) Health Campus / Munirah Mohamad - Mohamad, Munirah (Perpustakaan Tengku Anis, 2019)
The trainee as the final semester student of Bachelor of Science of Information System Faculty had decided to enroll at the Universiti Sains Malaysia (USM) Health Campus for the industrial training period which will take place from 1st February till 30th of June. During the time spent at this organization, the trainee had learnt a lot of things which is useful for the development of the trainee for the future. The trainee had learnt regarding the Codelgniter platform as a better PHP development framework. Besides, the trainee had also learnt about the formatting of computer, disposition of organization assets. The trainee was also being exposed with a lot of new things such the artificial intelligence and the enterprise architecture. Not forget to mention, the trainee also had the opportunity to see in live the usage of the teleconference meeting using some modern and advance devices available nowadays.